2014
DOI: 10.1093/annonc/mdu054
|View full text |Cite
|
Sign up to set email alerts
|

DOC-MEK: a double-blind randomized phase II trial of docetaxel with or without selumetinib in wild-type BRAF advanced melanoma

Abstract: DOC-MEK (EudraCT no: 2009-018153-23).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 18 publications
0
50
1
4
Order By: Relevance
“…MEK inhibitor activity in a strictly BRAF wild type melanoma population was assessed in a phase 2 placebo controlled trial of docetaxel with or without selumetinib [21]. Despite suggestions of increased activity for the combination, (the trial did not detect a difference in PFS or OS, attributed to the use of an inferior MEK inhibitor), PFS in the selumetinib arm (4.23 months) was less than the same figure in our study (5.5 months).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…MEK inhibitor activity in a strictly BRAF wild type melanoma population was assessed in a phase 2 placebo controlled trial of docetaxel with or without selumetinib [21]. Despite suggestions of increased activity for the combination, (the trial did not detect a difference in PFS or OS, attributed to the use of an inferior MEK inhibitor), PFS in the selumetinib arm (4.23 months) was less than the same figure in our study (5.5 months).…”
Section: Discussioncontrasting
confidence: 70%
“…In a placebo-controlled phase 2 study the combination of docetaxel and selumetinib given to patients with K-RAS mutant non-small cell lung cancer resulted in a significant improvement in progression free survival and overall response rate compared to docetaxel alone [20]. In a similar trial in BRAF wild type melanoma, non-significant increases in progression free survival and response rate were observed [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that resistance to MEK inhibition may occur via up regulation of AKT signalling and that combination therapy with both MEK and PI3K inhibitors may be beneficial [24,26], and investigations into this combination therapy continue [28]. The use of MEK inhibitors in combination with docetaxel has been investigated in phase II studies in melanoma [29] and NSCLC with indications that KRAS mutant NSCLC may be sensitive to the combination [30] and a phase III trial is underway to test the efficacy of the combination [31]. This Phase I study will inform the further development of WX-554 in phase II trials as a single agent and in additional Phase 1 combinatorial trials.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II trial, AZD, in combination with docetaxel, shows no significant improvement in progression‐free survival (PFS) compared to docetaxel alone in patients with wild‐type BRAF 30. In the opposite, improved PFS and tumor regression was observed with AZD when compared to chemotherapy in advanced uveal melanoma patients 31.…”
Section: Discussionmentioning
confidence: 99%